Diagnosis and Management Update of Hemoptysis - Rahman, MK; Rashid, MH; Khan, MMR; Tarik, H; Chowdhury, MMH; Alim, MA; Mahmood, I; Ekram, ARMS (TAJ: Journal of Teachers Association, 2009)
Hemoptysis is defined as the spitting of blood derived from the lungs or bronchial tubes as a result of pulmonary or ' bronchial hemorrhage1. Hemoptysis is classified as non-massive or massive based on the volume of blood loss; however, there are no uniform definitions for these categories. In this article, hemoptysis is considered non-massive if blood loss is less than 200 ml per day. The lungs receive blood from the pulmonary and bronchial arterial systems. The low-pressure pulmonary system tends to produce small-volume hemoptysis, whereas bleeding from the bronchial system, which is at systemic pressure, tends to be pro fuse. TAJ 2009; 22(1): 324-329